Translation of Functional Styles (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
On the basis of comparison the translation of texts of different functional styles the essence of adequate translation is specified, conditions for a holistic analysis of the original and the translation are formulated.
Keywords: scientific-technical style; functional style; journalistic style; the official business style; the scheme for text comparison